Analisis Yuridis dan Maqāṣid al-Syarī‘Ah Terhadap Hak Asuh Anak (Ḥaḍānah) Bagi Penyandang Penyakit Menular - Muda'i, Syaiful; Amin, M. Misbahul (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2025)
Every child has a fundamental right to receive proper care (ḥaḍānah) from both parents, encompassing physical, psychological, spiritual, and educational dimensions. In Islamic law, custody constitutes a moral and legal responsibility grounded in the principle of al-ḥifẓ wa al-ri‘āyah (protection and guardianship) for the child’s welfare. However, ethical and juridical issues arise when the custodian suffers from a contagious disease that may endanger the child’s safety. This study examines the status of ḥaḍānah for individuals with contagious diseases through a maqāṣid al-syarī‘ah approach, focusing on the protection of life (ḥifẓ al-nafs), lineage (ḥifẓ al-nasl), and intellect (ḥifẓ al-‘aql). Employing a normative research design with juridical-maqāṣidī approaches, the study finds that custody may be temporarily revoked if it poses a danger to the child but can be restored once the custodian recovers or ensures the child’s safety. The maqāṣid al-syarī‘ah framework reinforces justice, proportionality, and contextual child protection.